2012
DOI: 10.1177/0091270010397049
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of AR9281, an Inhibitor of Soluble Epoxide Hydrolase, in Single‐ and Multiple‐Dose Studies in Healthy Human Subjects

Abstract: AR9281, a potent and selective inhibitor of soluble epoxide hydrolase (s-EH), is in clinical development targeting hypertension and type 2 diabetes. The safety, pharmacokinetics, and pharmacodynamics of AR9281 were evaluated in double-blind, randomized, placebo-controlled, ascending, single oral dose (10-1000 mg) and multiple dose (100-400 mg every 8 hours for 7 days) studies in healthy subjects. AR9281 was well tolerated, and no dose-related adverse events were observed during either study. The drug was rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(112 citation statements)
references
References 23 publications
2
109
0
1
Order By: Relevance
“…Randomized double-blind, placebo-controlled studies in healthy volunteers have shown that AR9281 dose-dependently inhibits s-EH at doses that are well tolerated. 103 A randomized double-blind, placebo-controlled dose-ranging phase II study in patients with mild to moderate hypertension and impaired glucose tolerance was terminated in November 2009, and no efficacy results have been reported, suggesting that it was ineffective in lowering BP 104 (ClinicalTrials.gov: NCT00847899). However, s-EH inhibitors have other promising therapeutic applications, for example, inflammation, pain, and CVD that warrant future investigation.…”
Section: Soluble Epoxide Hydrolase Inhibitorsmentioning
confidence: 99%
“…Randomized double-blind, placebo-controlled studies in healthy volunteers have shown that AR9281 dose-dependently inhibits s-EH at doses that are well tolerated. 103 A randomized double-blind, placebo-controlled dose-ranging phase II study in patients with mild to moderate hypertension and impaired glucose tolerance was terminated in November 2009, and no efficacy results have been reported, suggesting that it was ineffective in lowering BP 104 (ClinicalTrials.gov: NCT00847899). However, s-EH inhibitors have other promising therapeutic applications, for example, inflammation, pain, and CVD that warrant future investigation.…”
Section: Soluble Epoxide Hydrolase Inhibitorsmentioning
confidence: 99%
“…There is potential therapeutic value of increasing EET activity for inflammatory and cardiovascular disease, metabolic syndrome, tissue regeneration, and pain management. sEH inhibitors have already been tested in human subjects and are undergoing continued development (Chen, Whitcomb, et al, 2012;Imig & Hammock, 2009). It is unlikely that the global reduction of EET metabolism by sEH inhibition will be without side effects, and there is concern that increasing EET levels will promote cancer (Panigrahy et al, 2011).…”
Section: Inflammation and Cancermentioning
confidence: 99%
“…As shown in Fig. 1, the CYP monooxygense pathway catalyzes the oxidation of arachidonic acid at any of the four double bonds to four regioisomeric epoxyeicosatrienoic acids (EETs) (5,8,11,and 14, by the CYP epoxygenase and/or 19-and 20-hydroxyl eicosatetraenoic acids by the CYP -hydroylase (34,47,95,106). EETs and 20-HETE have been identified as the main metabolic products of arachidonic acid in rodent and human tissues (47,117).…”
Section: Cytochrome P-450 Metabolitesmentioning
confidence: 99%
“…Inhibition of sEH also reduced the elevation of blood pressure in high-fat diet-fed rats and mice and other experimental models of metabolic syndrome (43,104). Clinically, the sEH inhibitor AR9281 has recently completed a phase IIA clinical trial in patients with mild to moderate hypertension and impaired glucose tolerance (14).…”
Section: Cardiovascular Effects Of Seh Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation